ACTIVITY-BASED COSTING IN ANALYSIS OF COMPUTER-ASSISTED TEST REGISTRATION RATES : (CASE STUDY IN POLYTECHNIC PUBLIC SERVICE AGENCY XXX) - Bagas Johantri (IPSAR (International Public Sector Accounting Review), 2023)
This study aims to discover whether the registration fee for computer-assisted test participants at a location is sufficient to cover the cost of administering the test and then to find out the factors dominating the determination of the rate. The Public Service Agency (BLU) is a government agency in providing services to the public in an effective, efficient and economical manner. This research is qualitative research with a case study approach. The data in this study are documents, financial data, and interviews. This research uses activity-based costing to calculate the service cost, while factor determination uses content analysis of interviews. The results showed that sixteen out of thirty test locations had lower registration rates than the test cost. The main factors that influence the determination of service rates are fairness and equal opportunity for participants. The result cannot generalize all conditions. This research shows that profit is not the main priority for BLU. Service expansion becomes prominent, although not all locations are financially profitable.